SHARK LONGLINE FISHERY IN TANJUNGLUAR-EAST LOMBOK - Dharmadi Dharmadi; Ria Faizah; Lilis Sadiyah (Indonesian Fisheries Research Journal, 2013)
Studies on artisanal shark fisheries in Tanjungluar - East Lombok were conducted during the year 2001-2011 (except in 2003 and 2007). A sampling method called “rapid market survey” method was employed to collect catch data from surface and bottom longlines fishing, rapidly. Biological data and fisheries data were collected during survey. Catch data for shark were also obtained from daily records filled by TPI officers in Tanjungluar between 2009 and 2010. The results showed that sharklongline fishing was conducted every month. The trend of shark catches relates to the number of fishing vessels, fishing ground, and weather conditions at sea. The period between July and September is a transitional season from East to West seasons. During this season, the wind strength is weakened and a good fishing season for the fishers. The lowest catch occurs in January (1.06 tonnes) and the highest catch in September with the total catch of 24.6 tonnes. Sharks caught by surface longline were dominated by Silky shark, Carcharhinus falciformis (40-90%) with the size range of 100-125 cm. The catch of bottom longline was mostly consisting of fish in mature condition that dominated by Grey reef shark (Carcharhinus amblyrhynchos), Common black tip shark (C. limbatus), Spot tail shark (C. sorrah), and Scalloped hammerhead shark (Sphyrna lewini), with the size range of 125-200 cm, 170- 250 cm, 100-150 cm, and 170-300 cm, respectively. Surface longline fishing occurs in the offshore waters in depth more than 200 m to 3000 m, whereas bottom longline fishing is operated at a depth of 50-100 m around islands.